Approach to Environmental Education in Early Childhood Education: Comparative Study in Teachers From Spain and Costa Rica - Lozano-Lucia, Oscar Raúl; Talavera-Ortega, Marta (Revista Electrónica Educare, 2024)
Objective. This paper analyzes the training received by early childhood education teachers during their university studies, as well as their valuation of natural spaces, to determine their qualification to teach environmental education (EE). It also considers the compulsory nature of teaching this subject in early childhood education centers and the general perception of the importance of environmental education as part of sustainable educational awareness. This analysis was conducted among in-service early childhood education teachers in Spain and Costa Rica to establish the differences and similarities in the approach to EE in both education systems. Method. A random and anonymous selection of educators from Spain and Costa Rica was conducted, comprising 199 and 63 participants, respectively. Teachers answered a validated online questionnaire adapted to the purpose of this research. Responses were statistically processed using SPSS and JAMOVI, taking into account possible differences not only between countries but also in aspects such as gender, age, and teaching experience. Results. Despite some significant differences, generally speaking, a globalized perspective of the various issues addressed is shared, emphasizing the need to enhance the initial training of teachers. Conclusions. The differences between countries are not decisive in practice, and many of the problems, shortcomings, and concerns are shared in both countries. An improvement in initial training and heightened awareness are required.